Development of Dl1.72, a novel anti-DLL1 antibody with anti-tumor efficacy against estrogen receptor-positive breast cancer - Silva, Gabriela (2021)
Funding Information: Funding: This research was funded by Fundação para a Ciência e Tecnologia, Portugal, grants PTDC/BBB-BMD/4497/2014 (to A.B.) and PD/BD/113987/2015 (to J.S.-D.), iBETXplore grants 3D-ABC-PI-717 (to G.D.) and BiACaT-HER2:JAG1 (to G.S.). iNOVA4Health—UIDB/04462/2020 and UIDP/04462/2020, a program financially supported by Fundação para a Ciência e Tecnolo-gia/Ministério da Ciência, Tecnologia e Ensino Superior, through national funds is acknowledged. Funding from the INTERFACE Programme, through the Innovation, Technology and Circular Economy Fund (FITEC), is gratefully acknowledged. Support was also provided by the Applied Molecular Biosciences Unit—UCIBIO, which is financed by national funds from Fundação para a Ciência e Tecnologia (UIDP/04378/2020 and UIDB/04378/2020). Funding Information: This research was funded by Funda??o para a Ci?ncia e Tecnologia, Portugal, grants PTDC/BBB-BMD/4497/20141 (to A.B.) and PD/BD/113987/2015 (to J.S.-D.), iBETXplore grants 3D-ABC-PI-717 (to G.D.) and BiACaT-HER2:JAG1 (to G.S.). iNOVA4Health?UIDB/04462/2020 and UIDP/04462/2020, a program financially supported by Funda??o para a Ci?ncia e Tecnologia/Minist?rio da Ci?ncia, Tecnologia e Ensino Superior, through national funds is acknowledged. Funding from the INTERFACE Programme, through the Innovation, Technology and Circular Economy Fund (FITEC), is gratefully acknowledged. Support was also provided by the Applied Molecular Biosciences Unit?UCIBIO, which is financed by national funds from Funda??o para a Ci?ncia e Tecnologia (UIDP/04378/2020 and UIDB/04378/2020). Publisher Copyright: © 2021 by the authors. Licensee MDPI, Basel, Switzerland.